Development of Analytical Methods for Determination of β-Carotene in Pumpkin (Cucurbita maxima) Flesh, Peel, and Seed Powder Samples - Mulu Hagos; Mesfin Redi-Abshiro; Bhagwan Singh Chandravanshi; Estifanos Ele Yaya (International Journal of Analytical Chemistry)
Vegetables are consumed worldwide in fresh as well as processed forms. Pumpkin is considered as an important vegetable due to its nutritional values. The objective of this study was to evaluate all the analytical parameters and improve the performance of the methods for the determination of β-carotene in pumpkin flesh, peel, and seed samples using UV-VIS, NIR, and FTIR methods. β-Carotene was measured at 453 nm using the UV-VIS method which showed linear range, 0.1 to 12 µg/mL; R2, 0.999; LOD, 0.034 µg/mL; LOQ, 0.1 µg/mL; RSD, 1.5% to 11%; and percent recovery, 83% to 93%. β-Carotene was also measured at 1415 nm using NIR and at 1710 cm−1 using FTIR spectroscopic methods. The NIR method exhibited linear range, 12.5 to 250 µg/mL; R2, 0.999; LOD, 3.4 µg/mL; LOQ, 10, µg/mL; RSD, 1.8% to 11%; and percent recovery, 92% to 96%, while the FTIR method exhibited linear range, 4 to 100 µg/mL; R2, 0.999; LOD, 1.3 µg/mL; LOQ, 3.9 µg/mL; RSD, 0.69% to 10%; and percent recovery, 95% to 96%. The characteristic analytical data indicated that any of the three newly developed methods could be used for the determination of β-carotene in the pumpkin flesh, peel, and seeds. Acetone was used as the extraction solvent for the UV-VIS and NIR spectroscopic methods, and acetonitrile was used as the extraction solvent for the FTIR method. Content of β-carotene was found higher in pumpkin peel (340–445 µg/g), followed by pumpkin flesh (317–341 µg/g) and pumpkin seed (12–17 µg/g) by the UV-VIS method. β-Carotene content was obtained ((376–451 µg/g) and (289–313 µg/g); (210–287 µg/g) and (102–148 µg/g)) using NIR and FTIR methods in pumpkin peel and flesh, respectively. β-Carotene was obtained higher from pumpkin peel by all the three methods than from pumpkin flesh and seed. The β-carotene content in the pumpkin seed was not detected by NIR and FTIR spectroscopic methods.